2019
DOI: 10.3390/w11081596
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Potential Mapping Using an Integrated Ensemble of Three Bivariate Statistical Models with Random Forest and Logistic Model Tree Models

Abstract: In the future, groundwater will be the major source of water for agriculture, drinking and food production as a result of global climate change. With increasing population growth, demand for groundwater has increased. Therefore, sustainable groundwater storage management has become a major challenge. This study introduces a new ensemble data mining approach with bivariate statistical models, using FR (frequency ratio), CF (certainty factor), EBF (evidential belief function), RF (random forest) and LMT (logisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 58 publications
2
39
0
Order By: Relevance
“…Previous studies indicated that groundwater potentiality increases with gentle slope and low topographic elevation areas owing to the longer residence time for water to percolate [156][157][158][159]. The first slope category (i.e., <10 • ) that has the gentlest slope and lowest topographic elevation was categorized within 'very high' groundwater potentiality owing to the nearly-flat topography that promotes high infiltration rates.…”
Section: Slopementioning
confidence: 99%
“…Previous studies indicated that groundwater potentiality increases with gentle slope and low topographic elevation areas owing to the longer residence time for water to percolate [156][157][158][159]. The first slope category (i.e., <10 • ) that has the gentlest slope and lowest topographic elevation was categorized within 'very high' groundwater potentiality owing to the nearly-flat topography that promotes high infiltration rates.…”
Section: Slopementioning
confidence: 99%
“…Random forest (RF) is one of the machine learning models that has been considered in environmental modeling in recent years owing to its simplicity, robustness, and capacity to deal with complex data 21 . According to the authors’ knowledge, although the RF model has not been implemented to assess areas susceptible to asthma, its good performance has been proved in other environmental fields, such as groundwater potential 33 , groundwater hardness 22 , flood risk 23 , and PM 10 risk 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Economic and demographic developments in the world in general and in Vietnam, in particular, are causing ever-increasing water demands [5]. Given the increased demand for water for various purposes (e.g., agriculture, industry, and human consumption), most of the groundwater water reservoirs have been over-exploited [6]. Thus, identifying areas with high groundwater storage potential is important for effective water resource management.…”
Section: Introductionmentioning
confidence: 99%